The complicated use of dupilumab in the treatment of atypical generalized pemphigus erythematosus: A report of two cases - Jie Chen; Siji Chen; Xia Wu; Xiaoyun Jiang; Yongdong Wang; Hao Cheng (Taylor & Francis Group, 2023)
Pemphigus is a rare autoimmune disease and has the potential to be fatal without treatment. Pemphigus erythematosus (PE) is a benign type of pemphigus foliaceus. Glucocorticoids and immunosuppressive agents are primary therapeutic modalities in pemphigus erythematosus, which may lead to considerable side effects. There is a growing need for new pemphigus therapies with fewer adverse effects. Dupilumab is a humanized monoclonal IgG4 antibody that inhibits the signaling of interleukin-4 (IL-4) and interleukin-13 (IL-13) and has been applied for atopic dermatitis and asthma. Recently, dupilumab was thought to be beneficial in aggressive refractory pemphigus vulgaris. We report two cases: a 39-year-old male and a 59-year-old woman diagnosed with PE with atypical clinical features. With dupilumab, patients' skin lesions significantly improved, and suitable maintenance glucocorticosteroid doses were reached. In conclusion, we reported the short-term effectiveness and safety of dupilumab in two cases of atypical generalized PE. As an adjunct, such a biologic agent is expected to be efficacious in pemphigus erythematosus.